Pengaturan Ganja Medis dalam Hukum Pidana: Perbandingan Internasional dan Implikasinya bagi Indonesia - Kamil, Muhammad Irfan; Sulistyanta, Sulistyanta (Indonesian Publication Center, 2026)
The regulation of cannabis in Indonesian positive law continues to classify *Cannabis sativa* as a Schedule I narcotic, prohibiting its use for medical purposes and creating legal issues when cannabis is used to address specific health needs. This study analyzes cannabis regulation in Indonesia and several other countries and examines the possibility of legalizing medical cannabis from the perspectives of criminal law and the right to health. Using normative legal research with statutory and comparative approaches, the study relies on literature review of legislation, court decisions, and relevant legal scholarship, analyzed systematically and prescriptively. The findings show that Indonesia maintains a repressive and prohibitionist approach under Law Number 35 of 2009 on Narcotics, which provides no legal basis for medical cannabis use. In contrast, countries such as Thailand, the Netherlands, and Turkey permit limited medical cannabis under strict state supervision. Constitutional Court Decision Number 106/PUU-XVIII/2020 affirms that legalization constitutes an open legal policy subject to legislative discretion based on scientific evidence. The study recommends revising Law Number 35 of 2009 to allow limited and controlled medical cannabis use, enhancing protection of the right to health and reducing criminalization. Its originality lies in integrating criminal law, human rights, and comparative law perspectives to support narcotics policy reform.